The title as a constituent and structural component of T. G. Shevchenko’s poetic works: general characteristics, specifics - Ruban, Alla (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The author of the article focuses on the paratextuality of "Kobzar" by T G. Shevchenko, particularly, on the relationship between the poetic texts of the collection and the titles. There made an attempt to classify the titles of the works from different positions. The poetic book of the well-known Ukrainian author includes 237 works, only 80 of them have material names. Materially expressed titles of poems, ballads and poems are in the researcher’s special consideration. The titles of T G. Shevchenko’s poetic works are diverse in terms of substantive and factual information: they indicate the characters of the work, the place of "action", determine the main image-symbol or artistic detail, indicate information about the time. Also, T. G. Shevchenko’s "Kobzar" presents trait names, symbolic names, attribute names, generalizations based on social phenomena, etc. Special attention is focused on the extratextual information of the titles, when their basis is not only the content of the work, but its associative connection with other aesthetic objects: allusions that testify to the connection with the folklore national-cultural context; allusions to the biblical text; allusions based on a connection with a specific person; borrowing titles; genre headings; names based on persistent phrases or aphorisms. In general terms, the author of the article analyzes zero titles. The characteristics of "technical" names by "theme" is presented (the lexical and syntactic features of the first phrase are used): name-phrases in which there is the author’s assessment and the assessment of the characters, there is a hint of philosophical reflections, landscape description, dreams, warnings, memories, etc. It is noted that this classification of zero titles is conditional and does not fully convey the philosophical content of the works, somewhat impoverishes their poetic symbolism and only to some extent adjusts to the previous perception of the text.